Instructed Reading and Vocabulary in Arabic as a Foreign Language: A Research Agenda - Amr Rabie-Ahmed; Ayman Mohamed (Journal of the National Council of Less Commonly Taught Languages, 2022)
Arabic is reported as one of the top ten languages taught in U.S. higher education institutions (Looney & Lusin, 2019; Ryding, 2018). This underscores the importance of establishing more elaborate and extensive research in Arabic second language acquisition (ASLA). Theories on input, intake, interaction, feedback, vocabulary processing, and learner cognition need to be redefined to serve Arabic-specific purposes; otherwise, Arabic teaching practice will continue to be informed by Western language paradigms (Ryding & Allen, 2013). In this paper, we propose several research tasks focusing on reading and vocabulary research in Arabic as a foreign language (AFL) to bridge the gap between research in ASLA and pedagogy. Through highlighting some pressing challenges reported by Arabic learners and teachers, we provide an overview of published research motivated by the given challenges.